Design and Construction of a Self-Driving Wheeled Vehicle Using Ultrasonic Sensors and an Arduino UNO Board - Ahmed Saed Ishleebtah; Nouri Ali Almabrouk Alhashi (المجلة الأفروآسيوية للبحث العلمي, 2024)
In this paper, a collision-avoidance robot was designed and built to move along a specific path, which consists of various directions. The robot is programmed to avoid collisions within the path and maintain a safe distance from the walls. To solve this problem, we used ultrasonic sensors to detect any obstacles and also to determine the distance between the robot and the walls.